A new storage and retrieval method to support editing operations in a multi-disk-based video server - Lee, CI; Chang, YI; Yang, WP (My University, 1996)
Since the storage ordering is assumed the same ns the retrieval ordering in all the previous storage placement strategies, there is a requirement of a large amount of file copying or merging operations when users insert/delete some data into/from the media data. The observation is also important for video applications because features, like video editing, require the support of random access on individual video frames. fn this paper, roe propose a new strategy for the insert/delete operations on continuous media that are striped into multi- disks without reorganization of the whole data. From our performance analysis and simulation, the proposed algorithms for insertion/deletion may require only some additional movement cost.